The Research on the Global Competitiveness of the Leading Russian Universities - V. S. Senashenko (Moscow Polytechnic University, 2018)
The article is a review of a monograph "The Global Competitiveness of Leading Universities: Models and Methods for Estimating and Forecasting" written by I.P. Boiko, V.G. Khalin, E.M. Anokhina. The book discusses the models and methods for university competitiveness assessment, approaches to the formation of university ranking, specific problems concerning improving of the competitiveness of Russian universities and the system of Russian higher education. The reviewed monograph will be useful to a wide range of readers who are interested in the development of the Russian higher education system.